Agent-based Simulation of Emergency Evacuation for Nuclear Plant Disaster - Na, Kyoungseok; Lee, Gyu M (International Journal of Industrial Engineering: Theory, Applications and Practice, 2017)
An effective and efficient emergency evacuation planning is critical to the safety and welfare of the residents or citizens in case of natural or artificial disasters. The recent nuclear reactor accident at Fukushima caused the residents at Gijang to be concerned about the safety of their local nuclear plants. The nuclear reactor-related accidents is very rare but may cause the serious consequences and last for significant period. We conducted the agent-based simulation studies of emergency evacuation for the Gijang area in case of nuclear plant disasters. The developed simulation tool can be used to validate various evacuation strategies and support well-designed preparedness.